Lionel-at-large - Krensky, Stephen (New York : Dial Books for Young Readers, 1986)
Lionel faces such ordeals as having to eat green beans, going to the doctor, and looking for the snake his sister lost in his room.
"First published in the United States of America by Dial Books for Young Readers, 1986"--T.p. verso.
Keywords: Family life -- Fiction